Non-organized learning: the rise of homeschooling in Hungary - Csovcsics, Erika (Autonomy and Responsibility Journal of Educational Sciences, 2022)
The demand for alternative forms of education has noticeably increased in Hungary due to the significant changes in the legislation on the conditions and content of education over the last decade. Beside the already well-known choice of alternative schools based on a large scale of reform pedagogical views, an increase in the number of homeschooled children has been experienced. As a result of a conscious choice by taking advantage of the legal opportunity, homeschooling as a new and more incentive possibility for learning is perceived to be more effective. This study provides a brief insight into the situation of the vaguely known homeschooling practice in Hungary referring to the international context and the underlying reasons coming from results of the limited research conducted so far.